Dionisian Art. Notes on Art in some posthumous writings of Nietzsche - Vásquez Tamayo, Carlos (Estudios de Filosofía, 2005)
The article dwells on four themes that sum up Nietzsche's interpretation of Art and it also dwells on the centralposition that this activity has in the overcoming of nihilism and the transvaluation ofall values. These themes are: the feeling of drunkenness, the tension between force andform, the notions of “classic” and “romantic”, and that which is tragic. It is all done in relation to the dionisian character of Art, which is a corner stone to determine the affirmative value of it as an activity and to determine the character of “appearance ofreality” to which it points out.